Characterization Of Stonvent Byproduct By Physical And Chemical Analysis - Nur Atiqah Binti Mohamad Aziz, Nur Atiqah (2011)
The objective of this project is, to analyze STONVENT byproduct and characterize it by chemical and physical properties. STONVENT byproduct is the precipitate from STONVENT which already absorbs CO2 and already reach the equilibrium condition.